Engineering a New Chloroplastic Photorespiratory Bypass to Increase Photosynthetic Efficiency and Productivity in Rice - Shen, Bo-Ran; Wang, Li-Min; Lin, Xiu-Ling; Yao, Zhen; Xu, Hua-Wei; Zhu, Cheng-Hua; Teng, Hai-Yan; Cui, Li-Li; Liu, E.-E.; Zhang, Jian-Jun; He, Zheng-Hui; Peng, Xin-Xiang (Molecular plant, 2019)
Over the past few years, three photorespiratory bypasses have been introduced into plants, two of which led to observable increases in photosynthesis and biomass yield. However, most of the experiments were carried out using Arabidopsis under controlled environmental conditions, and the increases were only observed under low-light and short-day conditions. In this study, we designed a new photorespiratory bypass (called GOC bypass), characterized by no reducing equivalents being produced during a complete oxidation of glycolate into CO2 catalyzed by three rice-self-originating enzymes, i.e., glycolate oxidase, oxalate oxidase, and catalase. We successfully established this bypass in rice chloroplasts using a multi-gene assembly and transformation system. Transgenic rice plants carrying GOC bypass (GOC plants) showed significant increases in photosynthesis efficiency, biomass yield, and nitrogen content, as well as several other CO2-enriched phenotypes under both greenhouse and field conditions. Grain yield of GOC plants varied depending on seeding season and was increased significantly in the spring. We further demonstrated that GOC plants had significant advantages under high-light conditions and that the improvements in GOC plants resulted primarily from a photosynthetic CO2-concentrating effect rather than from improved energy balance. Taken together, our results reveal that engineering a newly designed chloroplastic photorespiratory bypass could increase photosynthetic efficiency and yield of rice plants grown in field conditions, particularly under high light. A new photorespiratory bypass (GOC bypass), catalyzed by three rice-self-originating enzymes, i.e., glycolate oxidase, oxalate oxidase, and catalase, was designed and successfully established in rice chloroplasts. Transgenic plants carrying GOC bypass showed increased photosynthetic efficiency and productivity in rice under field conditions, with particular advantages under high light, which were found to be resulted from a photosynthetic CO2-concentrating effect.